2018
DOI: 10.1159/000487231
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mild Cognitive Impairment and Dementia in Saudi Arabia: A Community-Based Study

Abstract: Introduction: The age of the population in Saudi Arabia is shifting toward elderly, which can lead to an increased risk of mild cognitive impairment (MCI) and dementia. Objective: The aim of this study is to determine the prevalence of cognitive impairment (MCI and dementia) among elderly patients in a community-based setting in Riyadh, Saudi Arabia. Methods: In this cross-sectional study, we included patients aged 60 years and above who were seen in the Family Medicine Clinics affiliated with King Faisal Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 19 publications
5
59
3
Order By: Relevance
“…In addition, most of them were farmers (65.1%) and had a very low income (≤270 USD/month). The prevalence of MCI in our study was different from another study that had been conducted in central Thailand using 57.6% of people with MCI had an education of > 7 years [19]. However, the MoCA-B (Thai version) was already developed for screening MCI in illiterate and low education populations [18].…”
Section: Discussion/conclusioncontrasting
confidence: 80%
See 2 more Smart Citations
“…In addition, most of them were farmers (65.1%) and had a very low income (≤270 USD/month). The prevalence of MCI in our study was different from another study that had been conducted in central Thailand using 57.6% of people with MCI had an education of > 7 years [19]. However, the MoCA-B (Thai version) was already developed for screening MCI in illiterate and low education populations [18].…”
Section: Discussion/conclusioncontrasting
confidence: 80%
“…Memory problems in older people in our study were not a significant risk factor associated with MCI. Likewise, the results in Saudi Arabia reported only 37.4% had memory complaints and were not shown as a risk factor in their results [19].…”
Section: Discussion/conclusionmentioning
confidence: 81%
See 1 more Smart Citation
“…This population is susceptible to multiple vascular risk factors as well as a rising prevalence of neurocognitive disorders and stroke, with evidence of both small vessel disease and large vessel occlusion. 15,16…”
mentioning
confidence: 99%
“…A systematic review published in 2012 reported a prevalence of MCI ranging from 0.5% to 42% in different countries and populations [13] . Recent studies in the US [14] , Spain [15] , Brazil [16] , Saudi Arabia [17] , and Japan [18] reported a range of MCI prevalence between 6.5% and 38.6%. Great variations in reported prevalence of MCI also exist within China.…”
Section: Introductionmentioning
confidence: 99%